Outcomes and prognostic factors of cytoreductive surgery and perioperative intraperitoneal chemotherapy in high-volume peritoneal carcinomatosis - Lee S. Kyang; Suzannah L. Dewhurst; Valerie A. See; Nayef A. Alzahrani; David L. Morris (International Journal of Hyperthermia)
Background and objectives The management of patients with extensive appendiceal mucinous neoplasms and mesothelioma is controversial. Our aims were to analyze overall survival (OS), disease-free survival (DFS) and independent prognostic factors associated with high peritoneal cancer index (PCI) status in patients who underwent cytoreductive surgery (CRS) and perioperative intraperitoneal chemotherapy (PIC).Methods A prospectively-maintained database for patients with appendiceal neoplasms and mesothelioma undergoing CRS/PIC from year 1996 to 2018 was retrospectively analyzed. Patients who achieved complete cytoreduction were stratified into limited (PCI < 30) and extensive (PCI ≥ 30) disease groups.Results 260 female and 235 male patients were identified. The 5-year survival for low-grade appendiceal mucinous neoplasms (LAMN) was significantly higher in the low PCI group (96.2% vs. 63.5%, p < 0.001). There was no difference in the OS across both groups in high-grade appendiceal mucinous neoplasms (HAMN) (63 vs. 69 months; p = 0.942) and mesothelioma (72 vs. 42 months; p = 0.058). Overall mortality was 2%. Grade III/IV complications were significantly higher in extensive disease (68% vs. 36.6%, p < 0.001). On multivariate analysis, use of EPIC and blood transfusion (>8 units) were independent positive and negative prognostic factors, respectively, associated with OS. Meanwhile, use of EPIC conferred benefit in DFS while increased blood transfusion (>8 units) and elevated preoperative CA125 were predictive of a poor DFS.Conclusion Long-term survivals following CRS/PIC are achievable with acceptable mortality and higher morbidity rates in extensive appendiceal mucinous neoplasms and mesothelioma. High PCI status does not preclude treatment with CRS/PIC.